Connection between macroscopic kinetic measurables and the degree of rate control. Issue 18 (31st August 2017) - Jørgensen, Mikkel; Grönbeck, Henrik
Abstract : Macroscopic kinetic measurables are linked to elementary reaction steps by the degree of rate control. Abstract : Catalytic reactions are commonly characterized by measuring reaction orders and apparent activation energies. In the present work, these macroscopic measurables are related to the degree of rate control ( χ i ), which describes how the overall kinetics is influenced by the elementary reactions. The reaction orders are found to be χ i -weighted sums over the microscopic rates, derived with respect to pressure. Similarly, the apparent activation energy is shown to be a sum over the individual reaction-energy-barriers, weighted by χ i . The results couple macroscopic kinetics to the microscopic scale, which can facilitate analysis of catalytic reaction kinetics.